2017
DOI: 10.1021/jacs.7b08707
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl Cross-Coupling of Anomeric Nucleophiles: Scope, Mechanism, and Applications in the Synthesis of Aryl C-Glycosides

Abstract: Stereoselective manipulations at the C1 anomeric position of saccharides are one of the central goals of preparative carbohydrate chemistry. Historically, the majority of reactions forming a bond with anomeric carbon has focused on reactions of nucleophiles with saccharide donors equipped with a leaving group. Here, we describe a novel approach to stereoselective synthesis of C-aryl glycosides capitalizing on the highly stereospecific reaction of anomeric nucleophiles. First, methods for the preparation of ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 122 publications
1
70
1
Order By: Relevance
“…Beyondt he wide scope of acceptors tolerated by these conditions, Walczak and co-workersd emonstrated the method's utility in the synthesis of axinelloside Abuilding blocks [72] as well as in orthogonal glycosylation strategies employing anomeric nucleophiles as an ew typeofg lycosyl acceptor. [73] Despite the high yields afforded under the optimized conditions, anomeric selectivities were suboptimal with initial results showing a:b diastereoselectivities of 1:1.2. As highlighted at variousp oints in this review,a sw ell as in the seminalw ork published by Lemieux, [30] poor anomeric selectivities can often times be ameliorated by halide-ion assisted anomerization of the glycosyl intermediate and can result in more reactive b anomeric halides.…”
Section: Activation By Phosphorus:a Pplications Of Appel Mitsunobu mentioning
confidence: 97%
“…Beyondt he wide scope of acceptors tolerated by these conditions, Walczak and co-workersd emonstrated the method's utility in the synthesis of axinelloside Abuilding blocks [72] as well as in orthogonal glycosylation strategies employing anomeric nucleophiles as an ew typeofg lycosyl acceptor. [73] Despite the high yields afforded under the optimized conditions, anomeric selectivities were suboptimal with initial results showing a:b diastereoselectivities of 1:1.2. As highlighted at variousp oints in this review,a sw ell as in the seminalw ork published by Lemieux, [30] poor anomeric selectivities can often times be ameliorated by halide-ion assisted anomerization of the glycosyl intermediate and can result in more reactive b anomeric halides.…”
Section: Activation By Phosphorus:a Pplications Of Appel Mitsunobu mentioning
confidence: 97%
“…Anomeric stannanes are configurationally stable nucleophiles that can be stored and manipulated under ambient conditions without loss of stereochemical integrity, even after extended periods of time (6 months at room temperature or 1 year at −20°C). They can be easily prepared starting from the corresponding glycal 130 , affording either 1,2‐ cis or 1,2‐ trans glycosides, thus allowing formation of both C(1) anomers …”
Section: Exocyclic Oxygen Replacementmentioning
confidence: 99%
“…[20] With these conditions in hand, we were able to prepare as eries of linear and branched saccharides. [20] Given the ease with which anomeric stannanes can be elaborated into oligosaccharides using established glycosylation techniques, while maintaining their configurationals tability,t he utility of this class of reagents is not restricted to the preparation of simple building blocks and is viable for the preparation of more complex starting materials.…”
Section: Synthesis Of Anomeric Stannanesmentioning
confidence: 99%
“…We wondered if anomeric stannanes would be suitable for the preparation Cglycosides through astereoretentive process and thus focusing our initial work on establishing whether or not C1-stannanes could participate in the Stille reaction. [20,23] At the outset of these studies, we anticipated the competing b-elimination to plague the cross-coupling process. We found that removal of the C2 substituent and subsequentg lycal formation could be prevented by aj udiciouss election of the appropriate phosphine ligand.…”
Section: C-glycosidesmentioning
confidence: 99%
See 1 more Smart Citation